Evaluation of dentists' awareness of how to prescribe correct radiographs in Isfahan in 2010-2011 - Mojdeh Mahdizadeh; Moslem Fazaelipour; Asghar Namdari (Isfahan University of Medical Sciences, 2012)
AbstractIntroduction: Radiography has an important role in the diagnosis of diseases. Professional responsibility necessitates that dental practitioners have adequate and sound knowledge about the techniques to minimize the patient dose. The aim of this study was to evaluate the awareness of dental practitioners in Isfahan about how to prescribe correct radiographs in 2010-2011.Materials and Methods: In this descriptive/cross-sectional study data was collected by distributing questionnaires among 400 dental practitioners in Isfahan. The questionnaire consisted of three parts, including a description of various radiographic techniques in the form of awareness questions. Awareness of dental practitioners was evaluated in 25 different fields, including correct prescription of radiographs. Data was analyzed and compared between the fields under study by one-way ANOVA and independent t-test (p value < 0.05).Results: Of the 400 dental practitioners taking part in the study, 222 (55.5%) were males and 178 (44.5%) were females, with no statistically significant differences in awareness between them (p value = 0.094). The mean awareness grades of dental practitioners with job experiences less than 5 years and more than 5 years were 11.76 ± 2.58 and 10.4 ± 2.74, respectively, with statistically significant differences (p value > 0.001).Conclusion: The results of this study showed that the awareness of dental practitioners in Isfahan about correct radiographic techniques is less than the acceptable level. Therefore, it is necessary to increase their knowledge and awareness by continuous education programs. Key words: Awareness, Dental practitioners, Radiography